Cytomegalovirus reactivation in liver transplant recipients due to hepatitis C cirrhosis is associated with higher cardiovascular risk – an observational, retrospective study. (26th March 2018) - Aguilera, Victoria; Di Maira, Tommaso; Conde, Isabel; Fornés‐Ferrer, Victoria; Vinaixa, Carmen; Pallarés, Carmen; Carvalho‐Gomes, Angela; Cubells, Almudena; García, María; Rubín, Ángel; Benlloch, Salvador; Gonzalez‐Dieguez, Luisa; et al.
Summary: The association between cytomegalovirus (CMV) reactivation and cardiovascular risk has been reported in solid organ transplant populations; however, it has yet to be assessed in liver transplantation (LT). We aim to evaluate whether CMV reactivation is associated with cardiovascular events (CVE) in HCV‐LT patients. LT patients (2010 and 2014) due to HCV cirrhosis were included. Clinically significant CMV (CS‐CMV) was defined as viral load (VL) >5000 copies/ml, need of therapy or CMV disease. Baseline variables and endpoint measures (CVE, survival, severe recurrent hepatitis C, de novo tumors, and diabetes) were collected. One hundred and forty patients were included. At LT, a history of AHT was present in 23%, diabetes 22%, tobacco use 45%, obesity 20%, and renal impairment (eGFR < 60 ml/min) in 26.5%. CS‐CMV reactivation occurred in 25% of patients. Twenty‐six patients (18.5%) developed a CVE. Cox regression analysis revealed two factors significantly associated with CVE: Pre‐LT DM [HR = 4.6 95% CI (1.6, 13), P  = 0.004] and CS‐CMV [HR = 4.7 95% CI (1.8, 12.5), P  = 0.002]. CS‐CMV was not independently associated with the remaining endpoints except for survival ( P  = 0.03). In our series, CS‐CMV reactivation was associated with a greater risk of developing CVE, thus confirming data from other solid organ transplant populations and emphasizing the need for adequate CMV control.